(untitled) (Bangladesh Journal of Zoology, 2016)
Pesticide residues, specially the persistent organic pollutant (POP) were analyzed from some fish species of Rangpur floodplain, Bangladesh. Fish samples were extracted with ethyl acetate, cleaned by sulphuric acid and analyzed by gas chromatograph and gas chromatograph-mass spectrometer. Presence of endrin was detected in Taki fish (Channa punctatus) samples. Traces of other pesticides were also evident. This confirms the use of banned pesticide in the northwestern Bangladesh. We discussed some consequences of public health issues if these contaminantspasses through in the higher food chain from the wetland ecosystem. Bangladesh J. Zool. 44(1): 1-8, 2016